Sarcasm Analysis in Wednesday Series Episode1-5 - Pratiwi, Anugerah Armeylia; Weda, Sukardi; Burhamzah, Muftihaturahmah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study aims to explore the form of sarcasm in the Wednesday series and to investigate the use of sarcasm in the Wednesday series. To obtain data from this analysis, the researcher used a descriptive qualitative method. The researcher watched a Netflix series entitled Wednesday with the number of episodes taken by the researcher being 5 episodes, namely episodes 1-5. This Netflix series tells the story of a girl who is a descendant of the Addams family named Wednesday, she has a different personality from children in general, has an all-black fashion, is rude, and seems to have no empathy. The result of this thesis found that the use of propositional sarcasm in this series is more used than the other types, this types are found in 16 extracts, then the second rank that is most used by the characters in this series is lexical sarcasm, the researcher found 6 extracts in Wednesday series, then illocutionary sarcasm found in 5 extracts, and the last is illocutionary with 3 extracts. In the use of sarcasm types by each character of the Wednesday series, they mostly use sarcasm to ridicule, mock, stop an argument, and sometimes use sarcasm in a positive form such as praise, In addition, the Reasher found that there is a connection between culture and language. Keywords: Netflix, Wednesday, Sarcasm